Ensino de Geografia por investigação: raciocínio geográfico e espacialidade do fenômeno - Jackson Junio Paulino de Morais (2022)
This work aimed to investigate and understand how inquiry-based learning can favor the development of geographic reasoning, as well as the greatest contribution of geographic knowledge to its students: interpretations of the spatiality of the phenomenon in a geographic situation. Inquiry-based learning is considered a didactic approach that promotes questioning, planning, choosing problem situations, elaborating hypotheses and building explanations based on scientific evidence. The study, developed with students from the basic education network, focused on the investigation of the knowledge mobilized by the research subjects when analyzing a given geographic situation, in order to develop geographic reasoning and the interpretation of the spatiality of the phenomenon. Data were collected using a research instrument whose methodological approach was the elaboration and application of a didactic sequence applied to seven subjects, guided by a question about a given geographic situation. Data analysis took place in dialogue with the principles of content analysis (BARDIN, 2016), based on Dewey (1959) and Ausubel (1968) learning theories, theoretical frameworks for teaching Geography and geographic reasoning (ROQUE ASCENÇÃO , VALADÃO, 2014, 2016, 2017a, 2017b, 2018, 2020; PAULA, CASTELAR, 2020), and inquiry-based teaching (CARVALHO, 2013, 2015; SASSERON, 2015; SPRONKEN-SMITH et al. 2007, 2008, 2012), to make this tangle of theories and factors interact in order to favor the constructions of geographical interpretations in basic education and present a construct that can be called Inquiry-based learning of Geography. It was found that students, when operating with the principles of geographic reasoning, structurer and structuring concepts and the methodological tripod of Geography from a geographic situation to be investigated, were able to operate with investigative skills, in addition to developing and mobilizing reasoning geographic area for the construction of interpretations of the spatiality of the phenomenon.